Correction to Lancet Infect Dis 2022; published online May 26. https://doi.org/10.1016/S1473-3099(22)00133-5 (The Lancet Infectious Diseases, 2022)
For much of the 20th century, the field of bacteriology was dominated by a pathogen-centric view, which rightly focused scientific resources on identifying, characterizing, and eliminating the agents of infectious disease. However, this perspective has resulted in the relative neglect of abundant yet poorly characterized members of the human microbiota. Few genera embody this oversight more clearly than Prevotella. Despite being consistently found in high abundance across diverse human mucosal sites, including the oral cavity, airways, and vagina, the underlying physiological roles of the genus in both health and disease contexts remain largely unclear. This review traces the evolution of Prevotella research and classification, arguing that the traditional "friend or foe" dichotomy is insufficient. We contend that more mechanistic work at the species level is needed to elucidate the biology of Prevotella, especially after the most recent taxonomic reclassification. The knowledge derived from a mechanistic focus will offer profound benefits for understanding and treating complex polymicrobial diseases across multiple systems, including chronic respiratory infections, oral inflammatory conditions, and recurrent genitourinary dysbiosis.